2017
DOI: 10.1038/s41598-017-14825-8
|View full text |Cite
|
Sign up to set email alerts
|

85% internal quantum efficiency of 280-nm AlGaN multiple quantum wells by defect engineering

Abstract: In this study, high internal-quantum-efficiency (IQE) AlGaN multiple quantum wells (MQWs) were successfully demonstrated on low-defect-density AlN templates with nano-patterned sapphire substrates. These templates consisted of AlN structures with 0∼30 periods superlattices (SLs) by alternating high (100) and low (25) V/III ratios under a low growth temperature (1130 °C). Compared to conventional high crystal-quality AlN epilayers achieved at temperatures ≥1300 °C, lower thermal budget can reduce the production… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 26 publications
3
24
0
Order By: Relevance
“…Here, we used a C value of 1 × 10 33 cm 6 /s [37], which is consistent with the values reported and calculated in the literature. , which is comparable or higher to the reported values over nearly the entire DUV range [21,[38][39][40][41][42][43][44][45]. It has been demonstrated that by reducing the dislocation density from 1 × 10 10 cm −2 to 5 × 10 8 cm −2 , the can be improved from 1% to 60% for the conventional AlGaN QW structure [1].…”
Section: Efficiencies Of Algan-delta-gan Qwssupporting
confidence: 67%
See 1 more Smart Citation
“…Here, we used a C value of 1 × 10 33 cm 6 /s [37], which is consistent with the values reported and calculated in the literature. , which is comparable or higher to the reported values over nearly the entire DUV range [21,[38][39][40][41][42][43][44][45]. It has been demonstrated that by reducing the dislocation density from 1 × 10 10 cm −2 to 5 × 10 8 cm −2 , the can be improved from 1% to 60% for the conventional AlGaN QW structure [1].…”
Section: Efficiencies Of Algan-delta-gan Qwssupporting
confidence: 67%
“…As mentioned previously, by correctly selecting Al contents in both sub-QW and barrier, a large R sp value can be maintained over the entire emission range from λ = 230 nm to λ = 280 nm. This can allow for the attainment of 90% η RAD , which is comparable or higher to the reported values over nearly the entire DUV range [21,[38][39][40][41][42][43][44][45]. It has been demonstrated that by reducing the dislocation density from 1 × 10 10 cm −2 to 5 × 10 8 cm −2 , the η IQE can be improved from 1% to 60% for the conventional AlGaN QW structure [1].…”
Section: Efficiencies Of Algan-delta-gan Qwsmentioning
confidence: 69%
“…Fig. 14 summarizes the EQEs, wall-plug efficiencies (WPEs), and IQEs of the available data of commercial and laboratory DUV LEDs in a wavelength range between 200 and 310 nm 24 , 25 , 28 , 29 , 31 , 32 , 52 , 56 , 106 , 112 , 131 , 164 , 177 192 . The EQE and WPE obviously decrease rapidly as the wavelength gets shorter.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most fundamental and crucial issues is to improve the crystal quality of AlN basal layers. Starting with the substrate, systematic works have addressed the buffer techniques beneath the AlN epilayer, including reactive plasma deposited AlN nucleation layers 45 , 46 , low/high-temperature AlN buffer layers 47 , double AlN buffer layers 48 , superlattice (SL) buffer layers 49 , microtrenches 50 , 51 , nanopatterned sapphire substrates 52 , and nanopatterned AlN buffer layers 48 . In the growth process, epitaxial strategies have been proposed as migration-enhanced metal-organic chemical vapor deposition (MOCVD) 53 , migration-enhanced lateral epitaxial overgrowth of AlN 50 , and multilayered AlN 54 56 .…”
Section: Manipulation Of Fields Of Chemical Potentialsmentioning
confidence: 99%
“…In the DUV emission region, the highest external quantum efficiency was reported to be 20.3% at 275 nm achieved by using a serious features such as Rh mirror electrode and AlN template for a flipchip LED structure [5]. Moreover, a high enhancement in IQE was achieved by large misoriented sapphire substrate [6] and defect engineering [7]. These achievements are still unsatisfactory compared with the GaN-based blue light counterpart [8].…”
Section: Introductionmentioning
confidence: 99%